Congenital cholesteatoma of mastoid origin: A multicenter case series - Čvorović Ljiljana; Đerić Dragoslava; Vlaški Ljiljana; Dankuc Dragan; Baljošević Ivan; Pavićević Ljubomir (Vojnosanitetski Pregled)
Background/Aim. The mastoid is the rarest site for the onset of congenital cholesteatoma (CC). The symptoms are atypical and minimal. The aim of this multicenter retrospective descriptive study was to define this extremely rare condition and its clinical presentation, diagnosis and management. Methods. We analyzed data files for a 15- year period in 4 tertiary otology centers and discovered 6 patients with the diagnosis of CC of the mastoid. Results. The clinical presentation of CC varied from incidental findings in patient to patient with otogenic meningitis. The most common findings during surgical procedures were mastoid cortex erosion, sigmoid plate dehiscence, dural exposure and external canal wall destruction. Conclusion. CC of mastoid origin tends to occur in adult patients probably because of minimal symptoms and the delayed diagnosis. It can exist for years in a nonaggressive state and develop to giant sizes. In children it is almost incidentally diagnosed. Early imaging is necessary in order to prevent serious complication.